IMPLEMENTATION OF CHARACTER EDUCATION THROUGH THE VALUES EXEMPLARY TEACHERS, STUDENTS AND PARENTS IN EFFORTS TO STRENGTHENING PRIMARY STUDENTS CHARACTER - Minsih, Minsih; Diah U, Ratnasari; UK, Honest (JURNAL JPSD (Jurnal Pendidikan Sekolah Dasar), 2015)
ABSTRACT The purpose of this study was to find a model to strengthen character education in an environment with an informal approach in Surakarta Muhammadiyah Elementary Education. The main methods developed in this study is a qualitative descriptive-reflective. Data collection involved observations of active and in-depth interviews with teachers, parents / guardians, and elementary school students. Data were analyzed with snowball technic of analysis models Milles Huberman. This study has several indicators of achievement each year. In the first study, the indicator is expected to map the development of character education through informal approach applied in the Basic Education in Surakarta.Pendidikan character Muhammadiyah expected to not only become an issue that has not been realized in the world of education in primary schools. Mapping will be obtained, among others: (1) an understanding of the character education of primary school teachers, (2) an understanding of elementary school students about character education, (3) understanding of parents / guardians about character education, (4) the proper understanding of character education is taught in elementary school , (5) which has been implemented character education in elementary school. Results of this research can be applied in primary education environment, in accordance with the mission of the study program is organized PGSD service, cooperation and development education elementary school level.